Adopting Evidence-Based National Guidelines to Treat Hypertension in Three Hybrid Retail/Same-Day Access Clinics - Hunt, Ann Marie (My University, 2017)
The popularity of retail care clinics has skyrocketed in the past decade. Today, they are a viable industry with a significant impact on healthcare. These clinics are recognized as providing affordable, accessible, quality health care to patients/consumers who would otherwise have to visit the emergency room. Retail clinics have revolutionized health care access and delivery in the United States (U.S.) and represent an innovative and disruptive change in the health care industry. With the aging population in the U.S., chronic health problems, such as hypertension, continue to rise and health care disparities are widespread. In North Carolina, more than 36% of the population report that they have been told by a healthcare professional that they have high blood pressure. Many times, a visit to one of these clinics may be the primary encounter a patient has with a healthcare practitioner. Elevated blood pressure screening during these visits can potentially increase the patient’s knowledge and understanding of hypertension and encourage them to seek treatment. The purpose of the project was to educate providers on JNC 8 guidelines to increase adherence to the guidelines in these clinics. The project was implemented in three hybrid retail/same-day access care clinics operated by a health system in rural southeastern North Carolina, staffed primarily by nurse practitioners. Results showed that gentle reminders helped providers to adhere to the guidelines and that many patients who did not have a primary care provider (PCP) were scheduled with one during their clinic visit.
Keywords: Hypertension, Nurse Practitioner, Evidence-Based Guidelines, JNC-8, Retail Care, Same-Day Access Clinics